Influence of structural transformations on electric and magnetic properties of Fe81B13Si4C2 amorphous alloy - Minić D.M.; Plazinić M.; Živanić J.; Maričić A. (Science of Sintering, 2010)
The structural transformations of the Fe81B13Si4C2 amorphous alloy under nonisothermal as well as under isothermal conditions were studied. The amorphous alloy was stable up to a temperature of about 450ºC when the structural transformations began. The primary crystallization starts by forming Fe3Si as main phase (more than 80 wt %), and two minor phases Fe2B and Fe3B. With the increase of the temperature the phase composition as well as ratio of present phases is changed and above 600oC it was confirmed the presence only two stable phases, Fe3Si and Fe2B. It was shown that all observed structural transformations have significant influence on the electric and magnetic properties of alloy. The electric resistivity of the crystallized alloy is lower than the amorphous one. The crystallized alloy possesses better magnetic susceptibility and retains the ferromagnetic properties in whole investigated temperature range.